Effect of photobiomodulation in secondary intention gingival wound healing-a systematic review and meta-analysis - Pooya Ebrahimi; Mahdi Hadilou; Ferdos Naserneysari; Amirmohammad Dolatabadi; Rana Tarzemany; Nafiseh Vahed; Leila Nikniaz; Reza Fekrazad; Leila Gholami (BMC, 2021)
Abstract Background Photobiomodulation is widely being used to improve the wound healing process in dentistry and a vast majority of studies have proven its benefits. But there are plenty of knowledge gaps according to the optimal laser characteristics which should be used to maximize the healing effects of lasers. The goal of this systematic review and meta-analysis was to determine the effect of photobiomodulation (PBM) as an adjunctive treatment to periodontal therapies to evaluate secondary intention gingival wound healing and post-operative pain. Methods Five databases (PubMed, Embase, Scopus, ProQuest, and Web of Sciences) were searched up to November 30, 2020, for clinical trials that reported the result of the application of PBM on secondary gingival healing wounds and post-operative pain and discomfort after periodontal surgeries. Two independent reviewers selected the eligible studies and the outcomes of interest were extracted. The quality of eligible studies was assessed using the Cochrane Handbook for Systematic Reviews of Interventions. Results Ultimately, twelve studies were included in this review. The application of PBM as an adjunct to periodontal surgeries resulted in a significant improvement in wound healing indices. The Landry wound healing index at the 7th post-operative day was significantly improved (SMD = 1.044 [95% CI 0.62-1.46]; p < 0.01) in PBM + surgery groups compared to the control groups. There was also a statistically significant increase in the complete wound epithelialization (RR = 3.23 [95% CI 1.66-6.31]; p < 0.01) at the 14th post-operative day compared to the control groups. The methods used to assess the post-operative pain were heterogeneous, and therefore the results were limited which made the meta-analysis for post-operative pain assessment not possible. Conclusion Based on the results of this review, PBM can be effectively used as a method to improve secondary intention wound healing. High-quality randomized clinical trials, however, are needed in the future to identify the optimal PBM irradiation parameters and the effect of PBM on post-operative pain.